PENERAPAN ANALISIS SWOT DALAM MENINGKATKAN PENJUALAN UNIT REKONDISI ALAT BERAT MERK KOMATSU PADA PT.PAMAPERSADA NUSANTARA DISTTRIK BALIKPAPAN - Rahmani Rahmani; C. Prihandoyo; Nina Indriastuty; Nely Tangke Tangke Rante (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The research is intended to exploit the SWOT strategy implemented in an attempt to increase the sales of heavy equipment reconstruction units in P.T. Pamapersada Nusantara District Balikpapan. In this study, there were 10 employees who gave their statements. The sample method applied to this research is purposive sampling, which selects samples based on special consideration. IFAS and EFAS matrices are analytical tools used for internal and external analysis of the Company. The results of the research show that the use of SWOT analysis has successfully increased the sales of re-conditioning units of heavy equipment brand Komatsu in this company